Background and Principles of Liberalization of the Electricity Market in the Context of European Integration Intentions of Ukraine - Палійчук, У. Ю. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
This article reviews the features of regulatory policy in conditions of transition to new models of energy market functioning, in the context of liberalization and reforming in accordance with the European model, prerequisites for such a transition are defined . An important condition for the liberalization of energy markets is the introduction of legislation to reform the basis of energy pricing, finding the balance between social priorities and economic feasibility. The adaptation of Ukrainian legislation to EU energy legislation should facilitate the development of transparent and competitive energy market in Ukraine, integrated into the European. The functioning features of the current "energy pool" electricity market model are examined, as well as under the transition to a new model. It is established that the transition to a new model of the electricity market of Ukraine in renewable energy sector involves protection of state-guaranteed privileges for renewable energy, "green" tariff payment mechanism remains in accordance with the law.